Overexpression of the key genes in the biosynthetic pathways of lipid A and peptidoglycan in Escherichia coli. (8th June 2022) - Guo, Yong; Ji, Fan; Qiao, Jun; Dong, Xiaofei; Wu, Yuanming; Wang, Xiaoyuan
Abstract: Gram‐negative bacterium Escherichia coli has a tripartite cell envelope with a cytoplasmic membrane, a peptidoglycan layer, and an asymmetric outer membrane containing lipopolysaccharide in its outer leaflet. The biogenesis of peptidoglycan and lipopolysaccharide shares the same substrate UDP‐GlcNAc. From UDP‐GlcNAc, MurA catalyzes the first reaction for peptidoglycan biosynthesis, while LpxA catalyzes the first reaction for lipopolysaccharide biosynthesis. This study demonstrates that murA overexpression in E. coli MG1655 inhibited the cell growth and increased the cell length, whereas lpxA overexpression in MG1655 neither inhibited the cell growth nor increased the cell length. Further study showed that individual overexpression of the other eight genes encoding the enzymes to catalyze the initial reactions in the biosynthetic pathway of lipopolysaccharide did not inhibit the cell growth. When MG1655/pBad‐ lpxA, MG1655/pBad‐ lpxD, and MG1655/pBad‐ lpxH were transformed with pFW01‐ thrA*BC‐rhtC that contains the key genes for L‐threonine biosynthesis and transport, the L‐threonine production was increased. The L‐threonine production in MG1655/pFW01‐ thrA*BC‐rhtC /pBad‐ lpxH increased 46.1% as compared to the control MG1655/pFW01‐ thrA*BC‐rhtC /pBad.